Data acquisition for isfet PH sensor system by using seeeduino stalker as a controller: article / Muhammad Al Baqir Zinal Abidin - Zinal Abidin, Muhammad Al Baqir (2013)
This project is about data acquisition for ISFET pH sensor system by using Seeeduino Stalker as a controller. ISFET pH sensor formed with reference electrode, which the function of reference electrode is to replace the gate of ISFET, is used in this project. Readout interface circuit is also used to produce the voltage response that is obtained from the ISFET sensor. The data are collected from pH4, pH7 and pH10. ISFET pH sensor and reference electrode are placed inside the pH solution and connected with the readout circuit. The voltage response that is obtained from the output of the readout circuit is then saved in the memory card on the Seeeduino Stalker. Data collected from April to May 2013, showed that voltage response for pH 4 is higher than pH7 and pH10. The objective of this project is to develop a measurement setup to collect the data from ISFET experiment especially the voltage response for every pH and the data from the readout circuit. Overall, this project objective achieved after the pH sample was tested from April to May 2013. The setup is successfully developed as the voltage response for every pH solution is complete collected from April to May 2013 and is saved in the data logger by using Seeeduino Stalker as a controller.